Group cohesion and performance: A search for antecedents - Kaymak, Turhan (My University, 2011)
With the advent of more team based approaches in managing organizations the construct of group cohesion has gained in saliency as it has implications for both group and organizational performance, and also may positively influence individual job satisfaction. One can define group cohesion as the level of commitment members feel toward the group and the group's tasks. This phenomenon of is usually examined from the perspective on how it adds to, or detracts from, group and organizational performance. Some scholars maintain that a high level of group cohesion leads to enhanced performance through better communication, reduced conflict, more empathy, and greater organizational citizenship. On the other hand, group cohesion has sometimes been associated with negative performance, as sometimes a highly cohesive group may shun outsiders and new ideas, or even exhibit groupthink in some contexts. However, uncovering the conditions that promote the formation of group cohesion is a much understudied aspect of this construct. In light of this condition, we employ a structural equation modeling approach to examine a number of possible antecedents to group cohesion. The sample is comprised of fourth year university students who answered a questionnaire developed for this study. The antecedents employed in the model include the construct of collective self-esteem, which is composed of membership, private collective self-esteem, and importance to identify of the group, and one's past experience with groups. Specifically, the results indicate that the individual-level trait of collective self-esteem is a personal disposition that managers should consider when making decisions on group composition.
Soudr?nost skupin a v?konnost: Hledání p?edch?dc?
Keywords: Antecedents; Group cohesion; Performance